Naive and Memory CD4+ T Cells Are Differentially Affected in Indonesian HIV Patients Responding to ART - Tanaskovic, S.; Fernandez, S.; Saraswati, H.; Yunihastuti, E.; Gani, R.; Djauzi, S.; Price, Patricia (2016)
While most HIV patients beginning antiretroviral therapy (ART) with advanced immunodeficiency recover CD4+ T cell numbers, the profiles and functions of the newly acquired CD4+ T cells have not been monitored in a resource-limiting setting. In this study, HIV patients (n = 31) from Jakarta, Indonesia, were studied 9 months after commencing ART with nadir CD4+ T cell counts <200 cells/μL. All patients were hepatitis C virus (HCV) seropositive, but asymptomatic. Twelve healthy age-matched controls from the same community were included. CD4+ T cell subsets, immune activation (HLA-DR), and expression of the interleukin (IL)-7 receptor α chain (CD127) were quantitated by flow cytometry. Proliferation (expression of Ki67) was measured following in vitro stimulation (5 days) with anti-CD3 antibody or IL-7. Fifty-two percent of patients recovered CD4+ T cell counts >200 cells/μL over 12 months.At 9 months, patients had fewer naive and CD31+-naive CD4+ T cells, more effector memory (EM) CD4+ T cells, and higher HLA-DR expression on CD4+ T cells than controls. CD127 expression was low on all CD4+ T cell subsets except for naive cells, where it was similar to controls. Similarly, after anti-CD3 antibody or IL-7 stimulation, patients had lower Ki67 expression than controls in all subsets, except naive CD4+ T cells where it was normal or elevated. Overall in the first year of ART, patients had fewer naive and more EM CD4+ T cells. Ongoing immune activation and, antigen-driven stimulation and differentiation of naive T cells may reduce the naive T cell pool, while driving the maturation and accumulation of memory cells with proliferative defects.